Community Asset Empowerment In Vietnam: Stakeholder Engagement, Networking And Partnerships - Rika Dwi Ayu Parmitasari; Nurmiati Nurmiati; Eka Suhartini; Wahyudi Wahyudi (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of a country cannot be separated from the development of the community within that country. This study provides a practical model of the asset-based community development (ABCD) approach. A survey on community development in Vietnam is used as a basis for analysis to demonstrate the applicability of an integrated approach. The results of the research explain community vulnerability and a series of interrelated and multi-dimensional factors that contribute to poverty in the community. Research also shows the assets, capabilities, and activities of communities that enable them to cope and survive despite obstacles and disadvantages. The data also shows that the Asset Based for Community Development framework as part of integrated community driven development is a useful framework for understanding the strengths of vulnerable communities to plan and implement sustainable community development strategies..